2013
DOI: 10.2147/ndt.s45931
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic eye movement applications for psychiatric disorders

Abstract: ObjectiveThe study presented here analyzed the patterns of relationship between oculomotor performance and psychopathology, focusing on depression, bipolar disorder, schizophrenia, attention-deficit hyperactivity disorder, and anxiety disorder.MethodsScientific articles published from 1967 to 2013 in the PubMed/Medline, ISI Web of Knowledge, Cochrane, and SciELO databases were reviewed.ResultsSaccadic eye movement appears to be heavily involved in psychiatric diseases covered in this review via a direct mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 95 publications
1
37
0
1
Order By: Relevance
“…Activity here is negatively related to saccade latency, such that the higher the activity of the SC, the faster the saccade to a target (Bittencourt et al, 2013). Activity here is negatively related to saccade latency, such that the higher the activity of the SC, the faster the saccade to a target (Bittencourt et al, 2013).…”
Section: Smooth Pursuit and Saccadesmentioning
confidence: 84%
See 2 more Smart Citations
“…Activity here is negatively related to saccade latency, such that the higher the activity of the SC, the faster the saccade to a target (Bittencourt et al, 2013). Activity here is negatively related to saccade latency, such that the higher the activity of the SC, the faster the saccade to a target (Bittencourt et al, 2013).…”
Section: Smooth Pursuit and Saccadesmentioning
confidence: 84%
“…This technique is particularly fitted to ED populations, given the body checking behaviors often seen in this group. This would also be helpful in making comparisons across psychiatric disorders (Bittencourt et al, 2013;Rommelse, Van der Stigchel, & Sergeant, 2008). For example, protocols have been developed for studying saccadic eye-movements in order to improve reproducibility (Nij Bivjank et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that depression and other mood disorders are also associated with objective abnormalities in saccades, smooth pursuits, and visual processing. 5,33,38 Therefore, future studies are needed to evaluate whether baseline characteristics of vestibulo-ocular function among females and those with depression place these populations at an elevated risk of developing VOD following SRC. The results of this study are consistent with our previous study 12 and provide confirmatory evidence that VOD is commonly detected among pediatric patients with acute SRC and PCS and is associated with prolonged recovery and an elevated risk of developing PCS.…”
Section: Discussionmentioning
confidence: 99%
“…Given that eye movement statistics are altered in subjects with autism [38], attention deficit [39] or other neurological disorders [40], applying information theoretic analyses to these eye movements statistics could turn them into a powerful diagnostics for a variety of neurological disorders.…”
Section: Distribution Of Maximally Informative Eye Movementsmentioning
confidence: 99%